E-learning in physical education learning: How are students' perceptions during the COVID-19 pandemic? - Mansur, Maulana; Achmad, Irfan Zinat; Gani, Ruslan Abdul (Journal Sport Area, 2022)
In implementing e-learning, it demands readiness from the school as well as from its students, the most basic obstacle is the lack of communication media used by students and limited signals that affect students’ perceptions of physical education learning during the Covid-19 pandemic. This study aims to determine how big the perception of class VIII SMPN 2 Cariu is in learning physical education during the Covid-19 pandemic. This research is a quantitative descriptive research, the method used is a survey. Data collection techniques in the form of a questionnaire using a Likert scale test. The population used was class VIII SMPN 2 Cariu, totaling 97 students consisting of 50 male students and 47 female students. The sample used in this study were 97 students with a non-probability sampling technique and a saturated sampling technique. The data in the study were analyzed using descriptive statistics with percentages. The results showed that student’s perception of class VIII SMPN 2 Cariu in learning physical education in the new normal era was overall in the "Medium" category with a total of 42 students and a percentage of (43%). This means that students’ understand enough to take part in physical education learning in the new normal era. In terms of learning, students are quite helped to take part in physical education materials by utilizing E-Learning during the Covid-19 pandemic.